Successful Intubation with McCoy Laryngoscope in a Patient with Ankylosing Spondylitis - Subedi, A; Tripathi, M; Bhattarai, B; Pokharel, K; Dhital, D (Journal of Nepal Health Research Council, 2014)
Involvement of cervical spine in ankylosing spondylitis limits neck movement resulting in difficult intubation. We report a case of 45-yr-old lady of ankylosing spondylitis with restricted neck movement planned for emergency laparotomy. Grade 3 Cormack and Lehanelaryngoscopic view was observed with Macintosh laryngoscope and gum elastic bougie could not be negotiated. At second attempt with McCoy blade, the posterior commissure of the vocal cord could be visualized and intubation was successful. Thus, in absence of flexible laryngoscopes and when awake intubation is not feasible, McCoy blade should be considered an alternative than Macintosh blade to attempt intubation in patients of ankylosing spondylitis with restricted neck movement. Â Keywords: ankylosing spondylitis; McCoy laryngoscope; restricted neck movement